2012
DOI: 10.1021/pr3000464
|View full text |Cite
|
Sign up to set email alerts
|

Role-Shifting PKCζ Fosters Its Own Proapoptotic Destruction by Complexing with Bcl10 at the Nuclear Envelope of Human Cervical Carcinoma Cells: A Proteomic and Biochemical Study

Abstract: Many features of deadly human cervical cancers (HCCs) still require elucidation. Among HCC-derived cell lines, here we used the C4-I one since its quantitative gene expression pattern most closely mimics invasive HCCs, including protein kinase-Cζ (PKCζ) overexpression. Via proteomic, bioinformatic, and biochemical approaches we identified 31 and 33 proteins co-immunoprecipitating with PKCζ from nuclear membranes (NMs) of, respectively, untreated or VP-16-exposed C4-I cells. Such proteins belonged to eight func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 76 publications
2
28
0
Order By: Relevance
“…The detected interaction of PDK1 with Bcl10 was particularly noteworthy, as we had previously reported that increasing amounts of assembled PKCζ•Bcl10 complexes accrued at the NMs of VP16-treated C4-I cells (20,31). Therefore, in this study, we aimed to establish whether the specific knockdown of Bcl10 expression would hinder the assembly of PDK1•PKCζ complexes and, consequently, hinder the increase in PKCζ activity at the NMs of apoptotic C4-I cells.…”
Section: Bcl10 Knockdown Prevents Pdk1 From Linking With/activating Pmentioning
confidence: 87%
See 4 more Smart Citations
“…The detected interaction of PDK1 with Bcl10 was particularly noteworthy, as we had previously reported that increasing amounts of assembled PKCζ•Bcl10 complexes accrued at the NMs of VP16-treated C4-I cells (20,31). Therefore, in this study, we aimed to establish whether the specific knockdown of Bcl10 expression would hinder the assembly of PDK1•PKCζ complexes and, consequently, hinder the increase in PKCζ activity at the NMs of apoptotic C4-I cells.…”
Section: Bcl10 Knockdown Prevents Pdk1 From Linking With/activating Pmentioning
confidence: 87%
“…Equal amounts (10-20 µg) of protein from each subcellular fraction were determined by means of Bio-rad Protein Assay (Bio-rad Laboratories, Milan, Italy) and processed for western blot analysis as previously described (15)(16)(17)(18)20 ]-PKCζ (sc-101778), anti-Bcl10 (331.3 sc-5273 mouse monoclonal or H-197 sc-5611 rabbit polyclonal), anti-PDK1 (A-10; sc-17766) and anti-Lamin B1 (C-20; sc-6216; this antibody was used to reveal equal loading of proteins) (all from Santa Cruz Biotechnology, Inc.). The blots were then incubated with alkaline phosphatase-conjugated anti-mouse, anti-rabbit or anti-goat IgGs (Santa Cruz Biotechnology, Inc.) and stained with BCIP/NBT liquid substrate reagent or CDP-Star (both from Sigma-Aldrich).…”
Section: Isolation Of Nuclei and Nm Fractionsmentioning
confidence: 99%
See 3 more Smart Citations